2019
DOI: 10.1111/1460-6984.12476
|View full text |Cite
|
Sign up to set email alerts
|

Help‐seeking and people with aphasia who have mood problems after stroke: perspectives of speech–language pathologists

Abstract: Background: Access to treatments for mood disorders may pose a challenge to individuals with compromised communication ability. Speech-language pathologists (SLPs) have previously reported that their clients with aphasia decline formal psychological support; however, their role in their clients' help-seeking has not been explored. Aims: To investigate SLPs' perspectives on how they currently support help-seeking for mood problems in people with aphasia and factors they perceive to be impacting service uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 60 publications
(89 reference statements)
1
38
0
Order By: Relevance
“…There are also few psychological and pharmacological treatment approaches specifically validated on persons with CDs. 26,[38][39][40][41][42][43][44][45][46] The mainstay of psychological services is psychotherapy, also known as "talk therapy," 47 which poses inherent challenges for those with CDs. Fortunately, approaches are emerging in the aphasia population, with several new behavioral health approaches under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There are also few psychological and pharmacological treatment approaches specifically validated on persons with CDs. 26,[38][39][40][41][42][43][44][45][46] The mainstay of psychological services is psychotherapy, also known as "talk therapy," 47 which poses inherent challenges for those with CDs. Fortunately, approaches are emerging in the aphasia population, with several new behavioral health approaches under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid evidence review sources indicated the prevalence of poststroke depression as between 43% and 70% of stroke patients (Ashaie et al, 2019;Carota et al, 2016;Cobley et al, 2012;Døli et al, 2017;Hilari et al, 2010;Hunting Pompon et al, 2019;Kauhanen et al, 2000;Ryan et al, 2019;Shehata et al, 2015). Baker Kauhanen et al's (2000) 1-year prospective study evaluated the prevalence of post-stroke aphasia at three time points and found that non-fluent aphasic patients are particularly at risk of developing poststroke depression since they are more aware of their impairments (Kauhanen et al, 2000).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Furthermore, skills to provide psychosocial care while assessing patients is important; for example, speech-language pathologists (SLPs) may lack confidence and skills to provide sound psychological care and support aphasic stroke patients' needs (Baker et al, 2021;Ryan et al, 2019) determined that social workers may be preferred Stroke survivors should be assessed by trained personnel using a standardised and validated scale if altered mood is suspected (Stroke Foundation, 2017). However, there is no consistency regarding the roles and responsibilities of mood screening procedures and providing psychological care (Baker et al, 2020).…”
Section: Screening Perceptions and Psychological Care Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations